A Life-Cycle Theory Analysis of French Household Electricity Demand - Fateh Belaïd; Christophe Rault; Camille Massié (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper develops a pseudo-panel approach to examine household electricity demand behaviour through the household life cycle and its response to income variations to help strengthen the energy policy-making process. Our empirical methodology is based on three rich independent microdata surveys (the National Housing Surveys), which are representative of the French housing sector. The resulted sample covers the 2006-2016 period. Using within estimations, this paper finds striking evidence that the income elasticity of French residential electricity demand is 0.22, averaged over our four cohorts of generations. In light of other works, our estimate stands in the lower range. The empirical results also show that residential electricity consumption follows an inverted U-shaped distribution as a function of the age of the household's head. Most notably, it appears that households at the mid-point of their life cycle are relatively the largest consumers of electricity. This outcome has important implications for policy-making. Any public policy aimed at reducing household energy consumption should consider this differentiation in consumption according to the position of households over the life cycle, and therefore target as priority households at the highest level of consumption.
Keywords: C23; D12; Q21; Q41; 330; residential electricity demand; pseudo-panel; energy policy; France